Routing Quality of Service for Multipath Manets - Sultana , Ijteba; Bari , Mohd Abdul; Sanjay, Sanjay (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The purpose of adhoc network architecture is to enable internet access at any time, despite the absence Mobility and variability of infrastructure and base stations need a dynamic efficient routing system. To Choose a route depending on the rate a reactive congestion aware multipath routing protocol called RCRP was presented by us as a means of lowering energy consumption and speeding up the delivery of packets. It focuses on two crucial aspects of mantes: increasing network lifetime and preventing congestion. Based on current energy and traffic conditions, is a calculation that, Using the node's ERR and the packet's Pdt, we attempt to calculate the delay energy drain rate (d.e.d.r).Results from the simulations show that the work presented here improves upon previous versions of MM-AOMDV and AOMDV in terms of both network lifetime and end-to-end latency.